2020
DOI: 10.1165/rcmb.2019-0454oc
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis Reveals Mucociliary Remodeling of the Nasal Airway Epithelium Induced by Urban PM2.5

Abstract: Air pollution particulate matter ,2.5 mm (PM 2.5 ) exposure is associated with poor respiratory outcomes. Mechanisms underlying PM 2.5 -induced lung pathobiology are poorly understood but likely involve cellular and molecular changes to the airway epithelium. We extracted and chemically characterized the organic and water-soluble components of air pollution PM 2.5 samples, then determined the whole transcriptome response of human nasal mucociliary airway epithelial cultures to a dose series of PM 2.5 extracts.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 52 publications
1
19
0
Order By: Relevance
“…We next used the GEO database and PubMed to identify other studies that also performed transcriptomic analysis in bronchial epithelial cells after PM exposure ( Table 2 ). These studies utilized PM of varying size (2.5–10 µm) and from different locations [Saudi Arabia ( 15 ), China ( 11 ), United States ( 10 , 13 ), Italy ( 12 )], with treatments ranging from a concentration of 10–50 µg/cm 2 for 24 h. Excluding studies where data were incomplete or not publicly available, we compared the differentially expressed genes found in our study with those identified in other datasets ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We next used the GEO database and PubMed to identify other studies that also performed transcriptomic analysis in bronchial epithelial cells after PM exposure ( Table 2 ). These studies utilized PM of varying size (2.5–10 µm) and from different locations [Saudi Arabia ( 15 ), China ( 11 ), United States ( 10 , 13 ), Italy ( 12 )], with treatments ranging from a concentration of 10–50 µg/cm 2 for 24 h. Excluding studies where data were incomplete or not publicly available, we compared the differentially expressed genes found in our study with those identified in other datasets ( Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…We also treated cells directly with PM 2.5 dissolved in aqueous medium, and experiments performed using an air–liquid interface may produce different results, as suggested by other studies ( 44 , 45 ). Use of air–liquid interface may also obviate the need to account for how PM 2.5 is extracted, as varying levels of organic fractions has been shown to independently affect transcriptomic results ( 13 ). The lowest concentration we used was 1 µg/cm 2 , which was much lower than many other in vitro studies.…”
Section: Discussionmentioning
confidence: 99%
“…It is crucial to discuss which components of PM are responsible for the phenomena observed in this study. In fact, PM is composed of a wide range of chemicals and biological materials such as elemental carbon; organic carbon, including polycyclic aromatic hydrocarbons (PAHs); inorganic salts; metals, and lipopolysaccharide (LPS) (Honda et al, 2017;Montgomery et al, 2020). Notably, LPS has been associated with deleterious effects on respiratory health and immune function (Onishi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The positive relationship between the dose of P. parvum and the number of DEGs points towards an overall sensitivity of the gill transcriptome to toxic algae dose. Dose-dependent transcriptomic effects have also been demonstrated in the gut of Atlantic salmon exposed to plant proteins ( 49 ) and recently in human nasal airway epithelium cultures exposed to air pollution particulate matter < 2.5 μm (PM 2.5 ) ( 62 ). Furthermore, fish from HH and HM groups had not only twice more DEGs identified in their gills relative to LL fish, but also twice as many upstream regulators (26, 28 and 14, respectively) ( Figure 3B ) and twice as many downstream effects (28, 31 and 17, respectively) ( Figure 3C ).…”
Section: Discussionmentioning
confidence: 99%